CHARACTER BUILDING AND CREATIVITY IN EARLY CHILDHOOD THROUGH TOTAL PHYSICAL RESPONSE WARM UP GAME - Ririn Ambarini (Universitas Negeri Yogyakarta, 2017)
This study was aimed at determining the improvement of the character building and creativity levels of the students through TPR Warm Up Game. The study was action research including the activities of planning, implementation, data collection, and data analysis. The study was conducted in the second semester of the school year 2011/2012. The subjects were teachers and students of Class A of Doa Ibu kindergarten. Data were collected through observation, field notes, interviews, and documentation. The validity of the data was verified by triangulation. The data were analyzed using the descriptive qualitative flow model. Results show that there was an improvement in the character building and creativity levels of students after the implementation of the TPR Warm up Game. Improvement was also indicated by creative reactions, longer attention spans, self-confidence/organization, the expression of ideas, development of imagination, and increament of new vocabulary. The success of character building and creativity improvement is also supported by the methods of giving the opportunities for exploration and giving motivation in the form of praisesPENGEMBANGAN KARAKTER DAN KREATIVITAS ANAK USIA DINI MELALUI TOTAL PHYSICAL RESPONSE WARM UP GAMEPenelitian ini bertujuan untuk mengetahui peningkatan pengembangan karakter dan kreativitas anak melalui Total Physical Response (TPR) Warm Up Game. Penelitian ini merupakan penelitian tindakan kelas. Kegiatan penelitian meliputi perencanaan, pelaksanaan, pengumpulan data, dan menganalisis data/informasi. Pelaksanaan penelitian direncanakan pada Semester II Tahun Pelajaran 2011/2012. Subjek penelitian adalah guru dan anak didik kelompok A TK Doa Ibu, Kecamatan Tembalang, Semarang. Data dikumpulkan melalui observasi, catatan lapangan, wawancara, dan dokumentasi. Keabsahan data diperiksa dengan triangulasi. Data dianalisis secara deskriptif kualitatif model alur. Hasil penelitian menunjukkan bahwa ada peningkatan pengembangan karakter dan kreativitas anak melalui TPR Warm Up Game. Untuk meningkatkan pengembangan karakter dan kreativitas anak melalui TPR Warm Up Game juga didukung oleh beberapa indikator yaitu reaksi kreatif, rentang perhatian yang panjang, pengorganisasian diri/kepercayaan diri, mengaitkan ide atau gagasan/berekspresi, pengembangan imajinasi, dan penambahan kosakata baru. Selain itu, keberhasilan dalam peningkatan pengembangan karakter dan kreativitas juga didukung metode pendukung di antaranya adalah pemberian waktu untuk bereskplorasi dan pemberian motivasi berupa pujian